English Convents in Catholic Europe, c. 1600-1800. By James E. Kelly. Cambridge: Cambridge University Press, 2020. viii + 225 pp. $99.99 hardcover. - Lay, Jenna (Church history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS000964072100113X/resource/name/firstPage-S000964072100113Xa.jpg